Validation of the Chinese Version of the Schizophrenia Cognition Rating Scale - Huang, Kuan-Wei; Lin, Pao-Yen; Lee, Yu; Huang, Yu-Chi; Hung, Chi-Fa; Lee, Sheng-Yu; Chen, Chih-Ken; Wang, Liang-Jen (Psychiatry investigation, 2022)
Objective The Schizophrenia Cognition Rating Scale (SCoRS) is an interview-based assessment tool for evaluating the cognitive deficit and daily functioning of patients with schizophrenia.Methods Sixty-eight patients with schizophrenia and 68 age- and sex-matched healthy individuals were recruited to validate the Chinese version of SCoRS in this study. All participants underwent cognitive assessment using the SCoRS, which was verified by the Brief Assessment of Cognition in Schizophrenia (BACS), and the UCSD Performance-based Skills Assessment, Brief Version (UPSA-B). Patients with schizophrenia were additionally assessed using the Positive and Negative Syndrome Scale (PANSS).Results SCoRS ratings reported by patients (SCoRS-S), those reported by the interviewer (SCoRS-I), and SCoRS global scores (SCoRS-G) showed significant correlation with all subscales of the BACS and the UPSA-B. On receiver operating characteristic curve analysis, SCoRS-S, SCoRS-I, and SCoRS-G significantly differentiated patients with schizophrenia from healthy controls. Moreover, SCoRS-S and SCoRS-I ratings showed positive correlation with the negative symptoms and general symptoms of PANSS.Conclusion The Chinese version of SCoRS showed good discriminant, concurrent, and external validity, suggesting that it is a useful and convenient tool for assessment of cognitive function among Mandarin-speaking patients with schizophrenia in clinical practice.